Rethinking value investing for a global age - Towson, Jeffrey Alan, 1970- (FT Press Delivers elements., 2011)
This Element is an excerpt from What Would Ben Graham Do Now?: A New Value Investing Playbook for a Global Age (9780132173230) by Jeffrey Towson. Available in print and digital formats. How to adapt Ben Graham's powerful value investing approach for the realities of today's fast-shifting global markets. The world's tallest building is in Dubai, its largest phone company in China, its richest person in Mexico. The first truly global century arrived much faster than anticipated-and it's caught many smart investors flat-footed. Ben Graham's core concept of intrinsic value remains the anchor for investing in this new world. But today's general chaos presents growing challenges for traditional value methodology.